Melting heat transfer and MHD boundary layer flow of eyring-powell nanofluid over a nonlinear stretching sheet with slip - Reddy, N. Vijaya Bhaskar; Kishan, Naikoti; Reddy, Cherlacola Srinivas (Zielona Góra: Uniwersytet Zielonogórski)
The steady laminar incompressible viscous magneto hydrodynamic boundary layer flow of an Eyring- Powell fluid over a nonlinear stretching flat surface in a nanofluid with slip condition and heat transfer through melting effect has been investigated numerically. The resulting nonlinear governing partial differential equations with associated boundary conditions of the problem have been formulated and transformed into a non-similar form.
Keywords: Eyring-Powell fluid; melting heat transfer; MHD; nanofluid; stretching sheet; Brownian motion; thermophoresis